PRE-OPERATIVE BILIARY DRAINAGE IN THE PERIAMPULLARY NEOPLASIA - A SYSTEMATIC REVIEW - LUCENA,Gustavo Costa Marques de (2018)
ABSTRACT Introduction: Periampular neoplasms represent 5% of all cancers of the gastrointestinal tract with peak incidence in the 7th decade of life. The most common clinical picture is jaundice, weight loss and abdominal pain. Considering that cholestasis is related to postoperative complications, preoperative biliary drainage was developed to improve the postoperative morbidity and mortality of icteric patients with periampular neoplasias, whether resectable or not. Objective: To describe the outcome of patients with periampullary tumors undergoing preoperative biliary drainage with pancreatoduodenectomy. Method: The search was performed in the Medline/PubMed and Virtual Health Library databases by means of the combination of descriptors of the Medical Subject Headings. Inclusion criteria were clinical trials, cohorts, studies that analyze the morbidity and mortality of preoperative biliary drainage in Portuguese, English and Spanish. Exclusion criteria were studies published more than 10 years ago, experimental studies, systematic reviews and articles with WebQualis C or smaller journal in the area of ​​Medicine I or Medicine III. Of the 196 references found, 46 were obtained for reading with quality assessed through the Checklist Strengthening the Reporting of Observational Studies in Epidemiology. Eight studies were selected for review. Results: A total of 1116 patients with a sample ranging from 48 to 280 patients and a mean age of 48 to 69 years were obtained. Of the eight studies, four observed a higher rate of bleeding in drained patients; three a higher rate of positive bile culture in the intervention group; site and cavitary infection, and biliopancreatic leaks were more common in the drainage group in two studies each. The death outcome and rate of reoperation were observed in larger numbers in the control group in one study each. Conclusion: Preoperative intervention leads to a higher rate of infectious complications and bleeding.